ENGLISH PRONUNCIATION DIVERSITY PRODUCED BY INDONESIAN COVER-SINGERS: A CASE STUDY ON THE YOUTUBE CHANNEL - Ismi Maulina Utami (English Department of Faculty of Tarbiyah and Teacher Training, 2021)
This study focuses on the pronunciation changes of the Indonesian cover-singers on YouTube. It is qualitative research by using documentation technique. There were three subjects of this study namely RM with song “Memories”, AH with song “Thank You Next”, and HD with song “Comethru”. At the first singer’s pronunciation, there were 26 mispronounced words and she did consonant deletion, vowel shift, vowel coalescence, consonant neutralization, consonant insertion, and metathesis. At the second singer’s pronunciation, there were 17 mispronounced words and she did consonant deletion, vowel shift, consonant neutralization, consonant insertion, assimilation, and diphthongization. At the third singer’s pronunciation, there were 12 mispronounced words and she did consonant deletion, consonant neutralization, vowel shift, vowel coalescence, and consonant insertion. These pronunciation changes occur because of the distinction between the phonological system of English and Bahasa Indonesia , and the Indonesian cover-singers still rely on the word’s spelling rather than phonetic sound. Regardless of these two reasons, there are also several similarities in the phonological system between English and Bahasa Indonesia, but the Indonesian cover-singers still perform the pronunciation changes.